EFFECT OF ZIRCONIUM SILICATE CONTENT ON DIELECTRIC AND MECHANICAL PROPERTIES OF POLYURETHANE ELASTOMER - Zaharin, M.N.M.; Ku Ahmad, K.Z.; Othman, R.N.; Yahaya, R.; Tarawneh, M.A. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Polyurethane (PU) is an interesting polymer that possesses excellent high dielectric permittivity, low dielectric loss, and great flexibility, which makes it promising to be applied as a dielectric elastomer generator (DEG). However, enhancement in terms of dielectric permittivity is still necessary to ensure PU practicability in the industry. On the other hand, while holding the potential to considerably enhance polymer dielectric properties, the investigation of zirconium silicate (ZrSiO4) as a nanofiller for DE composites remains insufficient. In this paper, ZrSiO4 was incorporated with PU matrix to study the impact of ZrSiO4 nanofillers on PU composite dielectric, chemical, mechanical and morphology properties. ZrSiO4 nanofillers and PU matrix were synthesized through the melt-mixing method at various weight percentages (10 wt.%, 20 wt.%, 30 wt.%, 40 wt.%, and 50 wt.%). Fourier Transform Infrared Spectroscopy (FTIR) was used to investigate the chemical characteristic of the composite. The dielectric and mechanical characterization of the composites was also studied. The results from FTIR indicate that the ZrSiO4 nanofillers were successfully synthesized within the PU matrix. Other than that, at 50 wt.% of ZrSiO4, the PU/ ZrSiO4 recorded dielectric permittivity up to 12.07 (33.5% higher than pristine PU) while maintaining low dielectric loss and low conductivity. The ultimate tensile stress and elongation at the break of the PU composites were affected by the increment of ZrSiO4 contents but they still maintained excellent mechanical attributes. These PU/ZrSiO4 composites have the potential to be used as dielectric elastomers in the DEG application.